STRUGGLE IN DAVE PELZER’S NOVEL THE LOST BOY - Livia Zea Jesica Surbakti; Pardi Pardi (JOURNAL OF LANGUAGE, 2023)
This study aims at revealing struggle for life depicted in Dave Pelzer’s novel The Lost Boy. This study applied a qualitative research method in analyzing. Analyzing the data comprises gathering data, making interpretations, and writing reports. This research adopts theory pioneered by Maizler who divided struggle into four kinds: positive, negative, inevitable, and chosen. The results of the study show that there are two dominant struggles depicted in the novel, namely positive and inevitable struggles. Both positive and inevitable struggle are found dominantly in the novel. Positive struggle is portrayed by the protagonist who deals with identity confusion since he has to adapt and to fit in with new environment. Inevitable struggle is when the protagonist deals with necessary loses inevitably. The protagonist has to move many times until he found the warmth of family love. It can be concluded that the protagonist in the novel clearly deals with two kinds of struggle, but positive struggle is presented in the study since it can be found dominantly in the novel.